THE INFLUENCE OF DIABETES MELLITUS ON THE COURSE AND OUTCOMES OF MYOCARDIAL INFARCTION IN PATIENTS UNDERGOING PERCUTANEOUS CORONARY INTERVENTIONS - B. U. Mardanov; V. Е. Pyak; M. N. Korneeva; E. B. Akhmedova (Кардиоваскулярная терапия и профилактика)
Aim. To study the clinical course and outcomes  of myocardial infarction (MI) in diabetes  mellitus patients  (DM) and  non-diabetic,  underwent percutaneous coronary intervention (PCI).Material and methods. Totally, 99 MI patients included, that underwent PCI with stenting. Patients were selected to 2 groups by absence or presence of DM: group 1 (n=49) — DM type 2; group 2 (n=50) — non-diabetic  and glucose intolerance. We studied the baseline clinical and demographic,  as laboratory and instrumental characteristics of patients, specifics of in-patient stage of treatment and outcomes in 1 year after discharge.Results.  There  was  predominance   of  women  in DM2 group  and developing MI. It was found, that DM patients  adhered  the preclinical treatment  of ischemic heart disease  in 47% cases  and about 20% DM patients  did not take  glucose  lowering medications.  In patients  from group  1  the  arterial  hypertension  was  diagnosed  significantly more commonly in comparatively lower values of the left ventricle ejection fraction. More commonly than the other complication of MI, the acute heart failure developed (14%). By the end of the 1 year, DM patients nonsignificantly more  commonly  had  recurrent   hospitalizations  for  all cardiovascular causes, as the cases  with fatal outcomes.Conclusion. The course of MI in DM has its specifics as comparatively lower values of myocardium contractility, significant lesion of coronary vessels, high number of acute period of MI complications with indefinite influence on the one-year prognosis.